SEIZE THE ACTION OF THE INTERNATIONAL CRIMINAL COURT BY ITS COMPLEMENTARITY - Ovide Egide Manzanga Kpanya (Faculty of Law Universitas Lampung, 2019)
One of the most significant difficulties of the ICC is the absence of a universal acceptance and, in addition to the constant process of interference in internal affairs in which it is made. We are increasingly seeing the worsening of political critics who advocate, sometimes expressly vehemently, to quit its activities rather than optimizing its functioning. This situation maintains the vagueness of the international community in the fight against transnational crimes. However, suppose we want to fight the most serious crimes that threaten the peace and security of humanity by judicializing solutions. In that case, the complementarity of the Court, which is considered by these States to violate sovereignty, should instead be observed as a legitimate conventional motive that incites to improve the internal system and act effectively at the national level. States must combine both a feeling of preserving their State prestige, contained in the principle of sovereignty and the need to unbridle their national systems that have covered up the crimes that benefit them since the beginning of time.